2007
DOI: 10.1016/j.crci.2007.03.007
|View full text |Cite
|
Sign up to set email alerts
|

The use of glycolipids inserted in color-changeable polydiacetylene vesicles, as targets for biological recognition

Abstract: Topochemical organizations of conjugated diacetylenic acid photochemically polymerize to afford UVevisible absorbing polymers. Under the effect of an external stress caused by combination of the biomolecules to be recognized with the glycolipids on the vesicle surface, changes of conformation in the polymer backbone may result in a color change. Thus, monolayers and vesicles made of conjugated diacetylenic acid and a certain amount of glycolipids can be polymerized as far as the topochemical organization is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 66 publications
1
12
0
1
Order By: Relevance
“…Both suspensions exhibit a maximum absorption peak at 640 nm with a shoulder at 590 nm. These results indicate that even though CHO and SPH were incorporated into the vesicles, they did not affect the polymerization and the electronic transition, as Boullanger et al [28], Su et al [15] and Sun et al [29] have also observed. Lipid molecules form microdomains inside the PDA matrix; therefore, their incorporation does not affect the PDA electronic transition responsible for the blue color [30].…”
Section: Isothermal Titration Calorimetrysupporting
confidence: 65%
“…Both suspensions exhibit a maximum absorption peak at 640 nm with a shoulder at 590 nm. These results indicate that even though CHO and SPH were incorporated into the vesicles, they did not affect the polymerization and the electronic transition, as Boullanger et al [28], Su et al [15] and Sun et al [29] have also observed. Lipid molecules form microdomains inside the PDA matrix; therefore, their incorporation does not affect the PDA electronic transition responsible for the blue color [30].…”
Section: Isothermal Titration Calorimetrysupporting
confidence: 65%
“…Kew and Hall (2006) proposed that the change in colour due to pH is related to Coulomb repulsion among head groups, which can cause conformational disturbances in PDA structure. Boullanger et al (2008) suggested that increased pH leads to ionisation of PDA carboxyl groups, which induces some twists in polymer structure, thus reducing the activation energy required for colour change to begin. The results obtained for the effect of pH on the stability of PCDA/DMPC vesicles suggest that the conditions that expose vesicles to pH values above 9.0 can cause changes in the colorimetric properties of vesicles, while pH values lower than 4.0 may promote destabilisation of the vesicles.…”
Section: Effect Of Ph On the Stability Of Pcda/dmpc Vesiclesmentioning
confidence: 98%
“…The colorimetric response (CR) values were 26%, 44%, 38% and 33% at pH 9.1, 10.0, 11.0 and 12.2, respectively. Colorimetric response values P15% are visible to the naked eye (Boullanger et al, 2008). On the other hand, the addition of 0.1 M HCl (to give pH values of 5.4, 5.0, 3.5, 3.0 and 2.5) and acidification of the vesicles at pH values lower than 4.0 provided no change in the colorimetric properties of vesicles (there was no change in colour), but led to the formation of aggregates of vesicles and turbidity in the medium, which prevented spectrophotometric measurements.…”
Section: Effect Of Ph On the Stability Of Pcda/dmpc Vesiclesmentioning
confidence: 99%
“…Song, Cheng, Kopta, and Stevens (2001) highlight the importance of the pH. Kew and Hall (2006) and Boullanger et al (2008) suggested that the color change from blue to red is caused by the enhancement of the electrostatic repulsion among the head groups, also called Coulomb repulsion. NaOH cause increase in pH value leading to some twists in polymer structure that reduce the activation energy required for color change to begin [26][27][28].…”
Section: Resultsmentioning
confidence: 97%